POTENCY OF OIL SLUDGE INDIGENOUS BACTERIA FROM DUMAI-RIAU IN PRODUCING BIOSURFACTANT ON VARIATION OF SACCHARIDE SUBSTRATES - Ni’matuzahroh, Ni’matuzahroh; Yuliawati, Erta Tri; Kumalasari, Ditta Putri; Trikurniadewi, Nastiti; Pratiwi, Intan Ayu; Salamun, Salamun; Fatimah, Fatimah; Sumarsih, Sri; Yuliani, Hanif (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.636, 2017)
This study aims to detect the ability of four species of Dumai-Riau oil sludge indigenous bacteria to produce biosurfactants using 3 types of substrate (D-glucose, sucrose and molasses) and to determine the relationship between the five biosurfactant detection methods. The bacteria were grown on liquid mineral medium with addition of 2% saccharide substrates. The culture was incubated for 4 days at 30 0 C. Production of biosurfactants by bacteria is detected in various ways by indirectly evaluating the presence of biosurfactant in the culture supernatant by measuring the surface tension (mN / m), emulsification (%), oil spreading, drop collapse and knowing the bacteria's ability to lysis blood agar media. The study used a completely randomized design with 4 treatments and 3 replications. The data were analyzed descriptively and statistically using Anova and continued with Duncan test and Pearson correlation test was performed to test the correlation between methods. The results showed the four bacteria gave different growth responses when grown on different substrates. The ability of bacteria to produce biosurfactants also varies depending on the type of substrates. The result of surface tension method has correlation with result of oil spreading method, blood agar test and emulsification activity.